Hyperbaric Oxygen Therapy Can Induce Angiogenesis and Regeneration of Nerve Fibers in Traumatic Brain Injury Patients - Tal, Sigal; Hadanny, Amir; Sasson, Efrat; Suzin, Gil; Efrati, Shai (Frontiers in Human Neuroscience, 2017)
Background Recent clinical studies in patients with chronic neurological impairment due to stroke or traumatic brain injury (TBI) present evidence that hyperbaric oxygen therapy (HBOT) can induce neuroplasticity. Objective To assess the neurotherapeutic effect of HBOT in patients suffering from prolonged post-concussion syndrome (PPCS) due to TBI, using brain microstructure imaging. Methods Fifteen patients afflicted with PPCS were treated with 60 daily HBOT sessions. Imaging evaluation was performed using Dynamic Susceptibility Contrast-Enhanced (DSC) and Diffusion Tensor Imaging (DTI) MR sequences. Cognitive evaluation was performed by objective computerized battery (NeuroTrax). Results HBOT was initiated 6 months to 27 years (10.3±3.2 years) from injury. After HBOT, DTI analysis showed significantly increased fractional anisotropy values and decreased mean diffusivity in both white and gray matter structures. In addition, the cerebral blood flow and volume were increased significantly. Clinically, HBOT induced significant improvement in the memory, executive functions, information processing speed and global cognitive scores. Conclusions The mechanisms by which HBOT induces brain neuroplasticity can be demonstrated by highly sensitive MRI techniques of DSC and DTI. HBOT can induce cerebral angiogenesis and improve both white and gray microstructures indicating regeneration of nerve fibers. The micro structural changes correlate with the neurocognitive improvements.